Determinan Unmet Need KB Pada Wanita Menikah di Kecamatan Klabang Kabupaten Bondowoso (Determinants for Family Planning Among Married Women at Klabang Sub District in Bondowoso) - Ratna Katulistiwa; Ni'mal Baroya; Dwi Martiana Wati (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Unmet need for family planning is a multidimentional problem because it is influenced byvarious factors. Unmet need for family planning at East Java in 2013th was decrease from14,89% become 13,44%. But, the unmet need issue was enough higher than anotherprovince. Although, the unmet need issue in Bondowoso was high and Klabang sub districtwas higher than another distric in Bondowoso. This research aim to determine of unmetneed for family planning among married women, according to the demographiccharacteristic, social economic, and access in family planning services. This research wasanalytically, using cross sectional design. The number of samples was 219 respondentswho chosen by proportional random sampling technique. Bivariable analysis by Chi Squaretest and multivariable analysis by logistic regression (α=5%). There is a significant relationbetween the number of living children (OR=0,08), wealth status (OR=3,7), geographic orphysical accessibility (OR=0,19), psychosocial accessibility (OR=0,23), and cognitiveaccessibility (OR=3,84) with unmet need for family planning among married women.Keywords: Married women, unmet need, family planning